TANGGUNG JAWAB PENJUAL TERHADAP TANAH YANG BERSENGKETA - Manik, Rahmat GM; Hendra, Rahmad; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Land as a commodity that can be owned by the public, transferable ownership rights, one way transfer of land rights is through buying and selling. In the process of buying and selling land, the land status of the trade is very important. Because the common phenomenon of buying and selling land that was in dispute. The sale and purchase of land under customary law adopts cash, real and bright, meaning that every relationship should look real and concrete. Means of direct cash payments when buying and selling process, the real meaning of buying and selling land as a real object, and the light means buying and selling is done in front of the authorities. Today the frequent buying and selling land that is in dispute, of course it would be detrimental to the buyer. Land dispute itself has not decided who is entitled by law to have it, but routed through buying and selling. When there is a third party that will disturb the tranquility of the buyer to control the land he bought.Issues that will be examined in this study are: First, whether the land in dispute can be the object of buying and selling? Second, if the seller is responsible for the land in dispute?This research is a normative legal research. This discussion is more to discuss about an analysis of the law written in the book. Source of data used is the source of the data obtained from the study of literature, among others, include official documents, books, research results in the form of reports and so on. Data was analyzed qualitatively in drawing conclusions using deductive thinking.The results of this study are first, that the land was in dispute can not be transferred, because the land rights dispute itself is still up for grabs. Certainly not qualify agreement is valid lawful reason. Second, the seller is responsible in conflict over land dispute traded. Because the law states that the seller shall ensure and bear the traded goods. Advice from the author of First, the land in dispute should not be traded, because the rights of the land is not yet clear, Secondly, the land in dispute Seller shall be liable for damages arising from the sale and purchase of land in dispute.